Clilstore - Workshop - Silva, Ana Alexandra (2019)
The Tools for CLIL Teachers project has created a free online service where language teachers can author and share content-rich, multimedia learning units featuring the creator’s own choice of audio, video (e.g. from YouTube), text (e.g. a transcript) and images/graphics. No installation or setup of software is required. The authoring tools feature a unique and innovative element of functionality i.e. the ability to automatically link every word in a text to online dictionaries in over 100 languages. The teacher will have the choice of either sharing the resulting webpage online from the system’s repository or of sharing a link to the webpage on websites, via email or institutional VLEs, for example. The beauty of this system is that technical knowledge of FTP/URL and online publishing is not required. The online service also enables authoring of learning units from mobile devices (e.g. iPads) and is compatible with any operating system (Linux, Windows, MacOS, Unix etc.). The learning materials may also be accessed and used via smart phones, and materials may also potentially be authored from smart phones. We hope that the ability to access the learning materials from smart phones will encourage teachers to create materials. The user friendliness of the system also benefits teachers of mainstream languages and results in bespoke VOLL (Vocationally-Oriented Language Learning) and CLIL materials in the LWUTL (Less Widely Used and Taught Languages). The inclusion of Arabic also serves a large and growing target group teaching and learning that language. We are convinced that the online system, both the content authoring tools and the repository of materials, will be of huge benefit to educational institutions and learners alike, not least because the service is free of charge and open source (i.e. to enable future development). Crucially, the authoring tools and resulting content can be used from inexpensive mobile devices and older computers as they do not require high data processing capacity or bandwidth. This is a key factor in facilitating the adoption of technology, as there is no assumption that end users will need to acquire new hardware or upgrade their existing hardware in order to avail of the service. Such unseen costs frequently prevent the uptake of new technology and are a source of frustration for potential end users who recognise the benefits of new technology. Workshop Topics: Short presentation of the project ideas and objectives: Our understanding of CLIL Walkthrough of a sample unit made with Clilstore. The student perspective Walkthrough of Clilstore facilities. The author perspective How to get video, audio, and graphics for a unit